THE EFFECT OF COMPENSATION AND JOB SATISFACTION ON THE PERFORMANCE OF GRAB DRIVERS IN MAGELANG CITY - Muhammad Zaki Lathif; Axel Giovanni (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study aims to determine the effect of compensation, and job satisfaction on the performance of Grab drivers in Magelang City. The method in this study uses a quantitative descriptive method. The population in this research are all types of Grab Driver partners who are in the Magelang City area. The research sample was taken using a random sampling technique, where every individual in the population has the opportunity to be selected as the research sample. The sample used is 100 respondents. The results of the study show that simultaneous testing of the employee performance variables found that there was a significant effect. In the partial test it was found that the compensation variable had a positive and significant effect on employee performance, while on the job satisfaction variable it was found that there was a positive but not significant on the performance of Grab driver employees in Magelang City.